2013
DOI: 10.1186/1471-2229-13-39
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure assessed by SSR and SNP markers in a large germplasm collection of grape

Abstract: BackgroundThe economic importance of grapevine has driven significant efforts in genomics to accelerate the exploitation of Vitis resources for development of new cultivars. However, although a large number of clonally propagated accessions are maintained in grape germplasm collections worldwide, their use for crop improvement is limited by the scarcity of information on genetic diversity, population structure and proper phenotypic assessment. The identification of representative and manageable subset of acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
258
5
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(318 citation statements)
references
References 73 publications
48
258
5
7
Order By: Relevance
“…A population structure and genetic diversity based on 1,537 elite maize inbred lines using 359 SSR and 8,8244 SNP markers found the total gene diversity was 0.69 for the SSRs and half as much (0.32) for the SNPs (Inghelandt et al, 2010). A similar result was found in 2273 accessions of domesticated grapevine analyzed using 22 common SSR and 384 SNP markers, the average genetic diversity was higher for SSR loci (0.81) than for SNPs (0.34) (Emanuelli et al, 2013).…”
Section: Resultssupporting
confidence: 61%
“…A population structure and genetic diversity based on 1,537 elite maize inbred lines using 359 SSR and 8,8244 SNP markers found the total gene diversity was 0.69 for the SSRs and half as much (0.32) for the SNPs (Inghelandt et al, 2010). A similar result was found in 2273 accessions of domesticated grapevine analyzed using 22 common SSR and 384 SNP markers, the average genetic diversity was higher for SSR loci (0.81) than for SNPs (0.34) (Emanuelli et al, 2013).…”
Section: Resultssupporting
confidence: 61%
“…Additional phenotypic information was not enough available to help building the core collections despite it can help to optimize further screening and analyses of agronomical traits (Nicolaï et al 2013). In grapevine, Emanuelli et al (2013) compared a phenotypic and a genetic core collection. They showed that the latter retained more genetic diversity while maintaining a similar phenotypic variability.…”
Section: Definition Of Inra Diploid Core Collections For Association mentioning
confidence: 99%
“…The ∆K statistics provided the highest value at K = 2 (∆K = 82.59). As the ad hoc statistic ∆K preferentially detects the uppermost level of structure [47,48], K = 2 was considered as the starting point for the first ground clustering in all 343 individuals. Structure analysis identified two subgroups among the breeding parents.…”
Section: Discussionmentioning
confidence: 99%